MODERN STANDARDIZED METHODS OF MEASURING THE SELF-CONCEPT OF JUNIOR SCHOOL AGE CHILDREN - Orlova, Hanna (Mountain School of Ukrainian Carpaty, 2020)
The article states that one of the most important tasks of the educational process is the education of a holistic personality, the disclosure of personal potential and the consideration of the individual capabilities of each child. An important prerequisite for this task is the education of a positive self-concept of children, which is the basis of their self-determination, attitude towards themselves, interaction with peers and adults. The self-concept is a rather complex, multi-level personal formation and defines the life path of a person. The process of nurturing the self-concept requires an individual approach to children, which is why high-quality and timely diagnosis of self-concept in schoolchildren, the selection of appropriate methods are important for further education of positive ideas about themselves and self-perception. The publication states that the study of features of the child's self-concept is of great importance, and therefore the development of appropriate diagnostic methods and techniques. Children come to the first grade with the basics of selfperception and self-concept already laid down in preschool age, on which the individualized education of their I concept in school should be based. Prominent among the methods of research are standardized tests that allow you to quickly study the peculiarities of children's development and to compare the obtained indicators with the normative data in a well-established procedure. Ukrainian educators and psychologists use techniques developed by both domestic and foreign authors. Domestic and post-Soviet methods are more widespread in the territory of Ukraine, while not all foreign ones have become widespread, which partially limits the diagnostic tools of practitioners. The article deals with the twelve most popular methods of measuring the self-concept of children: Rosenberg Self Esteem Scale, Self Esteem Inventory, Piers-Harris Children’s Self Concept Scale, Tennessee Self Concept Scale, Self Perception Profile for Children, Self Description Questionnaire, Self Perception Profile for Adolescents, Pictorial Scale of Perceived Competence and Acceptance for Young Children, Hare Self Esteem Scale, State Self Esteem Scale, Multidimensional Self Concept Scale, Martinek-Zaichkowsky Self Concept Scale for Children. The analysis shows that all methods have good indicators of validity, reliability and internal consistency. Some of them have been translated and adapted into Russian or Ukrainian. However, in most cases information about the psychometric properties of adapted versions of the methods is not disclosed by the authors. Only several versions of the Harter Self Perception Profile are presented in a format that allows their practical application. In addition, a number of methods (the Rosenberg test and the different versions of the Harter method) have good prospects for implementation in the educational process with proper standardization and additional studies of validity and reliability.